Eudajmonizm w dobie pokolenia Z. Rozważania aksjologiczne - Grzesiak, Emilia (Studia Edukacyjne, 2020)
Grzesiak Emilia, Eudajmonizm w dobie pokolenia Z. Rozważania aksjologiczne [Eudaimonism in the Era of Generation Z. Axiological Considerations]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 267-296. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.15 This article deals with the category of happiness and its importance and role for the young people in the 21st century. Happiness in this dimension, however, is not understood as a state of satisfaction (in the individual dimension), but as a goal to which we aspire in our life. The text presents an axiological presentation of the issue, and the considerations cited in the article were referred to one of the ethical positions, which is the idea of eudaimonism.